Profitability of the Three Types of Smallholder Pig Farming in Indonesia: An Adaptation of Enterprise Budgeting Method - Ester Nurani Keraru; Harianto Harianto; Yusalina Yusalina (Buletin Peternakan, 2021)
This study aims to analyze the production cost structure and to measure the profitability of three types of smallholder pig farming, namely farrow-to-finish, pig-finishing, and pig-nursery in Indonesia. This study employed the data from the Statistics Indonesia-Livestock Business Household Survey (ST2013-STU). The measurement of profitability was carried out by calculating the profitability of three types of pig farming business using the adapted enterprise budgeting method. Based on the production cost structure, the percentage of pig feed costs accounted for more than 70% of the total cash of the three types of pig farming. The percentage of unpaid labor costs is more than 50% of the total non-cash. Based on the measurement results of the profitability indicators, it can be shown that the pig-finishing  type has the highest profitability among the three types of smallholder pig farming. Government policies are needed to increase pig farmers' access to financing and better pig farming technology.